2-(3,5-Dioxo-4-azatricyclo[5.2.1.02,6]dec-8-en-4-yl)acetic acid - Mehmet Akkurt; Aliasghar Jarrahpour; Pouria Shirvani; Muhammad Nawaz Tahir (Acta Crystallographica Section E, 2013)
The asymmetric unit of the title compound, C11H11NO4, contains two molecules, A and B, with different conformations: in molecule A, the norborne and carboxylic acid groups lie to the same side of the heterocycle, whereas in a molecule B, they lie on opposite sides. In the crystal, the A molecules form R22(8) carboxylic acid inversion dimers, linked by pairs of O—H...O hydrogen bonds. The B molecules link to one of the ketone O atoms of the A molecule by an O—H...O interaction, resulting in tetramers (two A and two B molecules). The tetramers are linked by weak C—H...O interactions, generating a three-dimensional network.